Vaccine potential of Haemophilus pleuropneumoniae oligosaccharide-tetanus toxoid conjugates. - Fenwick, B W (1986)
Oligosaccharides of smooth-type lipopolysaccharide (LPS) and oligosaccharides of rough-type LPS were isolated from Haemophilus pleuropneumoniae and conjugated to tetanus toxoid by reductive amination. The antigenic and immunogenic characteristics of the oligosaccharides, the oligosaccharide-tetanus toxoid conjugates, and the LPS of H. pleuropneumoniae were determined by passive hemagglutination, enzyme-linked immunosorbent assay, and inhibition enzyme-linked immunosorbent assay with antisera produced by immunization of rabbits and pigs. The findings were compared with the immunologic response induced by immunization of pigs with an H. pleuropneumoniae whole-cell vaccine and by infection of pigs with viable H. pleuropneumoniae. The results show that conjugation of isolated oligosaccharides of H. pleuropneumoniae to tetanus toxoid improves the immunogenicity of the oligosaccharides without significantly altering their antigenic character. These findings extend the understanding of the immunobiology of H. pleuropneumoniae infection in pigs and suggest the potential of purified oligosaccharides as vaccines to prevent porcine pleuropneumonia.